Implementation of Word Search Games in Arabic Vocabulary Learning for Taufiqurrahman Integrated Islamic Elementary School Students - Fahira Azzahir, Syifa; Rachmawati, Miatin (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Learning Arabic in Integrated Islamic Elementary Schools holds significant importance in the context of religious education and character development of children. Although Arabic is a mandatory language for Muslims, students often face challenges in learning it. The role of schools, especially for Integrated Islamic Elementary School, in overcoming these challenges is crucial by building better learning effectiveness through a comprehensive, interactive, and enjoyable approach for students to increase their interest in learning Arabic. The use of technology such as educational apps or games can also be an effective means to strengthen students' language skills. Through this approach, it is expected that students can overcome difficulties in learning Arabic and gain a better understanding of Islam.